Exciccates of Josef Paczoski collection from Odessa Mechnikov National University’ Herbarium (MSUD) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
There was considered the exsiccates’ composition from Paczoskiy collection which are presented by 86 examples from 80 species with 14 varieties, 57 (58) genus and 26 (27) families, which were gathered in 1893-1909. All plants characterize Poland and Bessarabian floras in that time frontiers. There was analyzed systematical spectrum, places of plants collection and collectors, who took part in gathering of those plants. The rare and disappeared species are indicated.
Keywords: exsiccates, herbarium, MSUD, collection, J. Paczoski.